Assessing the effects of vector control on dengue transmission - Yang, Hyun Mo; Ferreira, Claudia Pio [UNESP] (Elsevier B.V., 2008)
The dengue virus is an arbovirus transmitted to humans through mosquito Aedes aegypti. To describe the dynamics of dengue disease within these two populations we develop a compartment model taking into account chemical controls and mechanical control applied on the mosquitoes, which are the currently available controlling mechanisms to prevent dengue disease. To mimic seasonal variations, some parameters of the model are allowed to depend on time in order to divide a calendar year in favorable and unfavorable periods regarded to the development of vector population. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: mathematical modelling; dengue transmission; mosquito dynamics; control strategies; control efficacies